Lectin binding patterns and immunohistochemical antigen detection in placenta and lungs of Brucella abortus-bovine infected fetuses - Fiorentino, María Andrea (2018)
Lectin binding relies on the affinity of these substances for specific terminal sugars. The method facilitates the identification of complex structures to which the terminal sugar attaches and may reveal physiological or pathological changes in cells, intracellular interactions or extracellular transport pathways. This study was carried out to investigate the effect of infection with Brucella abortus on the pattern of lectin binding in bovine fetal lungs (n=6) and bovine placentas (n=5). Fetal lungs and placenta from heifers experimentally inoculated with B. abortus, strain 2308 were examined by histological, lectin-histochemical, immunohistochemical and cultural techniques. B. abortus antigens were immunohistochemically detected in fetal lungs and placenta. An increase in the labeling with UEA-1, DBA, PNA, RCA-1 and SBA was found in the lungs and an increase in the labeling with UEA-1, ConA, PNA, DBA was found in the placentas. The present lectin histochemical study revealed a distinctive pattern of oligosaccharide distribution in the lungs and placenta of B. abortus-infected fetuses